Itch in dermatomyositis: the role of increased skin interleukin‐31. (1st September 2018) - Kim, H.J.; Zeidi, M.; Bonciani, D.; Pena, S.M.; Tiao, J.; Sahu, S.; Werth, V.P.
Summary: Background: Interleukin (IL)‐31 is implicated in pruritus associated with pruritic skin diseases like atopic dermatitis. Although pruritus is a prominent feature in dermatomyositis (DM), few studies have evaluated the pathogenesis of DM‐associated itch. Objectives: To establish the prevalence of itch in DM, and to investigate the role of IL‐31 in DM‐related itch. Methods: Pruritus and disease activity of DM were evaluated by a visual analogue scale (VAS) and the Cutaneous Disease and Activity Severity Index (CDASI), respectively. Expression of IL‐31 and IL‐31 receptor alpha (IL‐31RA) in lesional DM, nonlesional DM and healthy control skin was evaluated by quantitative reverse‐transcriptase polymerase chain reaction and immunofluorescence. Flow cytometry was performed on skin cells isolated from lesional DM skin to identify cellular sources of IL‐31 in DM. Results: Among 191 patients with DM, 50·8% had moderate‐to‐severe itch, and itch was correlated with increased cutaneous severity ( r = 0·34). In patients with itchy DM, gene expression of IL31 and IL31RA in lesional skin was upregulated compared with nonlesional skin and healthy control skin. IL31 mRNA expression positively correlated with VAS itch score ( r = 0·67). On immunofluorescence, immunoreactivity for IL‐31 and IL‐31RA was stronger in lesional skin. Flow cytometry showed that lesional DM skin contained significantly more IL‐31‐producing cells, and CD4 + cells were the most common cell type. Lenabasum, an emerging treatment for DM, significantly downregulated IL‐31 from CpG‐stimulated peripheral blood mononuclear cells. Conclusions: Increased skin IL‐31 may play a role in DM‐associated itch, and ongoing trials will evaluate the effects of systemic treatment on IL‐31 and itch in DM.